Quorum sensing inhibition activities of Philippine ethnobotanicals against virulence factors in Staphylococcus aureus - Barrogo, K. N.; Jacinto, W. R.; Cruz, K. G. (International Journal of Agricultural Technology, 2021)
Quorum sensing (QS) and quorum sensing-inhibition (QSI) compounds hold a promising approach in combatting pathogenic diseases without the development of resistant strains. The global concern on rising antibiotic resistance paved the way for tapping natural products for their QSI activities. Natural products are ideal sources of QSI compounds that have the potential to inhibit QS regulation in bacteria. Ten ethnobotanicals namely Ageratina adenophora (Spreng.) R.M.King & H.Rob. (Panawel), Alstonia scholaris (L.) R. Br. (Palay), Ayapana triplinervis (Vahl) R.M.King & H.Rob. (Pantallion), Bidens pilosa L. (Anwad), Cestrum nocturnum L. (Dama de noche), Derris elliptica (Wall.) Benth. (Opay), Oreocnide trinervis (Wedd.) Miq. (Lal-latan), Pittosporum pentandrum (Blanco) Merr. (Lahwik), Sarcandra glabra (Thunb.) Nakai (Hag-ob), and Lipang daga (without known scientific name) were evaluated for the occurrence of QSI activity against Staphylococcus aureus PNCM 1582. Disk diffusion assay was tested the antibacterial activity of the methanolic extracts. In the absence of antibacterial activity, the methanolic extracts that were incorporated into the growth media were evaluated for QSI against the expression of virulence factors; DNase and α-hemolysin, of S. aureus PNCM 1582. Three methanolic extracts, B. pilosa, C. nocturnum, and P. pentandrum, showed antimicrobial activity against S. aureus PNCM 1582. Extracts of O. trinervis and D. elliptica showed QSI against DNase production. No methanolic extracts inhibited the α-hemolysin production in S. aureus PNCM 1582. The result represented possibilities for future studies on the biological activities of these plants. These plants are probable sources of natural products against QS to develop drugs against bacterial pathogens without developing resistance